Joint association between physical exercise, caffeine intake, and biological ageing: A cross-sectional analysis of population-based study - Guang Chen; Shichen Zhou; Yunqing Xun; Tung Leong Fong; Guoyi Tang; Jingyi Wang; Hongzheng Li; Xiangjun Yin; Jialiang Gao; Guanghui Zhu; Ying Wu; Jinlin Li; et al. (PLoS ONE, 2025)
Background Ageing is a significant risk factor for age-related diseases, accounting for 51% of global total disease burden. As thus, promoting healthy ageing is crucial. Although several potential anti-ageing drugs show promise, none have been approved for anti-ageing purpose. The World Health Organization (WHO) recommends physical exercise exceeding 600 metabolic equivalent of task (MET) minutes per week for adults. However, whether physical exercise positively impacts healthy biological ageing remains unclear. Objective This study aimed to investigate the joint correlation between MET level, caffeine consumption, and biological ageing. Methods We analyzed data from seven survey cycles (2007–2020) of the National Health and Nutrition Examination Survey (NHANES), involving 23,739 participants. Physical activity levels were measured in MET minutes per week, and biological ageing was assessed using both the PhenoAge and ENABL Age algorithms. Generalized linear regression for survey data was employed to test correlations, adjusting for confounding factors. A cubic spline model was used to detect non-linear relationships. Pre-specified subgroup analyses explored effect modifications, while predefined sensitivity analyses confirmed the robustness of the results. Results Each 100-MET increase in weekly physical exercise was associated with a 0.2-year delay in biological ageing (p < 0.001 for both PhenoAge and ENABL Age). Individuals with less than 600 MET minutes of weekly exercise had a higher risk of accelerated ageing compared to those exceeding 600 MET minutes (mean difference [MD]: 2.2 PhenoAge years, 95% CI [1.5–2.8], p < 0.001; MD: 2.1 ENABL Age years, 95% CI [1.1–3.1], p < 0.001). A L-shaped association was observed, with diminishing benefits of delayed ageing beyond 292 MET minutes for PhenoAge and 259 MET minutes for ENABL Age. Daily caffeine intake did not modify the correlation between MET levels and biological ageing (p for interaction > 0.05). Stronger effects were observed in non-Hispanic Black individuals, those with obesity, and low-income populations, but no benefit was found in cancer patients. Conclusions Our findings highlight a positive correlation between higher levels of weekly physical exercise and delayed biological ageing. However, the benefits plateau beyond specific MET thresholds. Caffeine intake does not influence this relationship. These results underscore the importance of promoting physical exercise at appropriate MET levels as a strategy for healthy ageing management in the general population.